COUNSELING USING COLLAGE MEDIA ON KNOWLEDGE OF HOW TO MAINTAIN DENTAL AND ORAL HEALTH - R, Herlina; Setiawaty Ningsih, Neny; Maryani, Yeni; Susatyo, Jojok Heru; Pakpahan, Omry (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Dental and oral health is a crucial aspect of overall health that affects an individual’s quality of life. Based on Health Law No. 36 of 2009 and various literature, the importance of dental and oral care is often not well understood by the public, especially elementary school children. This study aims to evaluate the effectiveness of dental and oral health education using collage media for fourth-grade students at SD Negeri 09 Pemangkat. This study employs a quasi-experimental method with a One Group Pretest-Posttest design. It measures students’ knowledge about dental and oral health care before and after receiving education using collage media. The study sample consisted of fourth-grade students who were given a pretest before the education and a posttest after the education. The results show that before the education, 33.3% of students had insufficient knowledge, 67.7% were in the moderate category, and no students were in the good category. After the education, students' knowledge improved with 3.3% in the insufficient category, 36.7% in the moderate category, and 60.0% in the good category. The average knowledge score of students before the education was 23.4, while it increased to 19.6 after the education. This study indicates that education using collage media is effective in enhancing students’ knowledge about dental and oral health care. Therefore, this method can be integrated into school health education programs as an effort to increase children's awareness and understanding of the importance of maintaining dental and oral health.